Impact of Raoiella indica Hirst (Acari: Tenuipalpidae) Infestation on Nitrogen Concentration of Areca catechu L. - Prabheena P; Ramani N (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Different tenuipalpid phytophagous mites might infest the foliage and nuts of the areca palm and cause significant damage. Raoiella indica (Hirst), has been known as a serious pest of areca palm. In the present study, concentration has been fixed on exploring the feeding impact of R. indica through the quantitative estimation of nitrogen concentration of mite-infested and uninfested leaves by ‘Kjeldahl method (1883)’. Results of the study have exposed that the feeding activity of the mite on the leaves of A. catechu has induced severe reduction in the levels of ‘total nitrogen’. The percentage loss of ‘total nitrogen’ was estimated to be 37- 62% in RPM-infested Areca leaves. Loss of nitrogen content as evidenced during the present study disclosed the potential of R. indica on A. catechu.